Long-term monitoring of bedload and debris flows in two small Alpine basins of different morphological s - Lenzi, M.A.; Mao, L.; Cavalli, M. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"Sediment transport in steep mountain streams can occur as bedload or debris flows, depending on basin geomorphology and sediment supply conditions. This paper compares two small catchments located in the Eastern Italian Alps (Rio Cordon and Moscardo Torrent) where the dominant sediment transport processes differ substantially. The former hosts a measuring station for water and sediment transport rates operating since 1986, whereas the latter was set up in 1989 to monitor debris-flow events. Differences in sediment dynamics between the two basins are quantitatively investigated by using a magnitude-frequency analysis that highlights the relatively low sediment supply of the Rio Cordon and the unlimited sediment availability in the Moscardo Torrent. This contrasting sediment transfer activity can be attributed to different basin and channel morphologies, which are analyzed in terms of sediment supply conditions and longitudinal profiles curves."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Sediment transport in steep mountain streams can occur as bedload or debris flows, depending on basin geomorphology and sediment supply conditions. This paper compares two small catchments located in the Eastern Italian Alps (Rio Cordon and Moscardo Torrent) where the dominant sediment transport processes differ substantially. The former hosts a measuring station for water and sediment transport rates operating since 1986, whereas the latter was set up in 1989 to monitor debris-flow events. Differences in sediment dynamics between the two basins are quantitatively investigated by using a magnitude-frequency analysis that highlights the relatively low sediment supply of the Rio Cordon and the unlimited sediment availability in the Moscardo Torrent. This contrasting sediment transfer activity can be attributed to different basin and channel morphologies, which are analyzed in terms of sediment supply conditions and longitudinal profiles curves.